Net consumption method does not provide helpful insights regarding the blue water footprint of hydroelectricity - Libor Ansorge (Elsevier, 2021)
Water footprint indicator describes direct and indirect use of waters for humanity. Three different methods are used to calculate the water footprint of electricity generation in a hydroelectric power station or the water footprint of processes associated with the operation of reservoirs. This article analyses a method referred to as “net consumption”, which assumes that, even before reservoir construction, there was evaporation from the area of a future reservoir. According to this method, water loss from the hydroelectric power station system is the difference between evaporation from the water reservoir surface and evaporation from the earth's surface before reservoir construction.The article presents several arguments as to why this method is wrong and should not be used as part of the methodology for calculating the water footprint of hydropower. The main arguments are: 1) the “net consumption” method does not describe the value of the water footprint of the product (i.e., consumption per unit of electricity), but the change in the water balance of the territory; 2) the “net consumption” method is not compatible with the methods of calculating the water footprint of similar products and water footprint methodology in general; 3) the “net consumption” method may lead to inappropriate conclusions about the sustainability of the construction and operation of a reservoir. The individual arguments are documented with examples.